Analisis Teknologi Blockchain Berperan dalam Meningkatkan Keamanan dan Data Privasi di Sektor Keuangan Terhadap Implementasi - Riskha Setianingsih; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
With the development of increasingly advanced technology, data security and privacy are becoming increasingly crucial issues in the financial sector. Blockchain technology has emerged as a promising solution to improve data security and privacy in this scope. This research explores the role of blockchain technology in strengthening data security and privacy in the financial sector through a qualitative research approach. By conducting literature analysis, it was found that blockchain technology offers characteristics such as decentralization, transparency, and cryptographic security that can significantly improve data security and privacy. However, challenges such as technological scalability and regulatory irregularities are still obstacles that need to be overcome for the implementation of this technology to be fully successful. A case study of blockchain implementation in the financial sector is also presented to illustrate its impact on data security and privacy. The research results show that although blockchain technology has succeeded in improving data security and privacy in the financial sector, further efforts are needed to optimally maximize its potential.